Study the Molecular Identification of Klebsiella Pneumonia Isolated From Different Patients in AL Diwaniya City - Jabr, Bahaa El_din Karim; Abd, Mustafa Hamid; Reda, Abdul khaleq Nazim Abdul; Chyad, Zainab Ali (American Journal of Biomedicine and Pharmacy, 2024)
This study was completed during a period of (15/11/2021) to (20/2/2022) in the bacteriology laboratories of the Gynecology Hospital in Qadisiyah Governorate. The aim of the study was to identify one of the types of Klebsiella bacteria, which is more susceptible to infection, men or women. Besides to knowing the severity of the infection. In addition to knowing pathogenicity and the gravity of its impact on the organs of the human body. From 30 samples isolated just seven samples were (23. 3%) diagnosed as klebsiella species, about four samples (57. 2%) has been diagnosed as klebsiella pneumonia that isolated from (urine (50%), blood (25%), sputum (25%)).